Hypersomnia and depressive symptoms: methodological and clinical aspects - Dauvilliers, Yves; Lopez, Régis; Ohayon, Maurice; Bayard, Sophie (BMC medicine, 2013)
The associations between depressive symptoms and hypersomnia are complex and often bidirectional. Of the many disorders associated with excessive sleepiness in the general population, the most frequent are mental health disorders, particularly depression. However, most mood disorder studies addressing hypersomnia have assessed daytime sleepiness using a single response, neglecting critical and clinically relevant information about symptom severity, duration and nighttime sleep quality. Only a few studies have used objective tools such as polysomnography to directly measure both daytime and nighttime sleep propensity in depression with normal mean sleep latency and sleep duration. Hypersomnia in mood disorders, rather than a medical condition per se , is more a subjective sleep complaint than an objective finding. Mood symptoms have also been frequently reported in hypersomnia disorders of central origin, especially in narcolepsy. Hypocretin deficiency could be a contributing factor in this condition. Further interventional studies are needed to explore whether management of sleep complaints improves mood symptoms in hypersomnia disorders and, conversely, whether management of mood complaints improves sleep symptoms in mood disorders.